Empirical vulnerability assessment for low rise RC, Timber and Masonry Icelandic buildings - Bessason, B; Ioannou, I; Kosmidis, I; Bjarnason, JO; Rossetto, T (The European Association for Earthquake Engineering, 2018)
The South Iceland Seismic Zone (SISZ) is about a 70-km long belt lying in the east-west direction and 10-15 km wide in the north-south direction. Approximately 20 earthquakes with magnitudes in the range of 6 to 7 have occurred in this zone since 1700. These events tend to occur in sequences and therefore structures may be exposed to strong ground motion from more than one event within a few days. The SISZ crosses the largest agricultural region in Iceland with small towns, farms and all the infrastructure assets of a modern society. On 17 and 21 of June, 2000, two Mw6.5 earthquakes struck the SISZ. Both were shallow strike-slip quakes with parallel fault ruptures and with an approximately 16 km fault-to-fault distance. They affected nearly 5000 lowrise residential buildings. All buildings in Iceland are registered in a detailed official inventory. Furthermore, all buildings are covered by compulsory catastrophic insurance and therefore, after the earthquakes, damage and repair costs for every damaged building were assessed for insurance purposes. The collected loss data merged with the real estate register data were used in the present study to assess a vulnerability model based on beta regression.Critical in the development of the methodology were the determination of which buildings sustained damage due to one or two events, secondly the problem of substantial variability in the loss data, and finally uneven spatial distribution of the buildings due to villages on one hand and single farms on the other hand.